Renal Abnormalities Caused by Canine Distemper Virus Infection in Terminal Patients - Silva, Mayra de Lima e; Silva, Gyl Eanes Barros; Borin-Crivellenti, Sofia; Alvarenga, Alef Winter Oliveira; Aldrovani, Marcela; Braz, Larissa Ayane do Nascimento; Aoki, Caroline; Santana, Aureo Evangelista; Pennacchi, Caio Santos; Crivellenti, Leandro Zuccolotto (Frontiers in Veterinary Science, 2022)
The aim of this study was to analyze the glomerular and tubular alterations in dogs with terminal distemper through light microscopy, immunofluorescence, and electron microscopy. Thirteen animals with a molecular diagnosis of distemper and neurological signs were selected. As a control group, 10 clinically healthy animals with no manifestations or signs of disease and with negative tests for Ehrlichia sp., Anaplasma sp., and Babesia sp. were included in this study. Renal tissue was evaluated by light microscopy, topochemistry for DNA/chromatin, and video image analysis to detect the nuclear phenotypes of the renal tubular epithelial cells (RTECs), immunofluorescence, and transmission electron microscopy. Results showed that dogs with distemper exhibited anemia, hypergammaglobulinemia, and proteinuria. Creatinine in the distemper group was lower compared to the control group (p = 0.0026), but there was no significant difference in relation to urea (p = 0.9876). Although this alteration may be due to the smaller muscle mass observed in animals with distemper, it probably is not of clinical importance. Glomerular and tubular lesions were confirmed by light microscopy in 84.6% of these animals. Additional findings in the animals with distemper included deposition of different classes of immunoglobulins, particularly IgM in 92.3% of the cases, fibrinogen deposition in 69.2% of the cases as assessed by immunofluorescence, alterations in the nuclear phenotypes of the RTEC characterized by condensation of chromatin, loss of DNA and reduction in the nuclear shape, and the presence of subendothelial and mesangial electron-dense deposits. These findings confirm the existence of renal alterations related to terminal distemper.